Analisis Alih Kode dan Campur Kode dalam Video Youtube Kenta Yamaguchi - Rasya Maulida; Sudjianto Sudjianto; Alo Karyati (IDEA : Jurnal Studi Jepang, 2021)
This study examines Code Switching and Code Mixing in Kenta Yamaguchi's Youtube Videos. The purpose of this study is to describe the form and causes of code switching and code mixing used by Kenta Yamaguchi in each of his videos. The data collection technique in this research is the free-of-conversation listening technique and the library study technique, namely by reading reference books related to Code Switching and Code Mixing, then watching a Youtube video hosted by Kenta Yamaguchi. The method that the author uses is a descriptive method, namely by setting several video parts to get data from Kenta's dialogue and analyze it. Based on the results of the analysis of 12 data found, there are 6 data in the form of code switching and 5 data in the form of code mixing. All forms of code switching are external code switching in the form of sentences and words. Factors causing code switching are third person factors, situations, listeners, wanting to show their identity and learning. The form of code mixing is in the form of word insertion elements, dialects and clauses. The causative factor of code mixing is the factor because it wants to show its learning, situation, habits and relaxation.